An ovine model for total hip replacement: operative procedure and complications - Field, J. R.; Aberman, H.; Carbone, A.; Sharpe, P.; Smith, N.; Dunlop, D.; Howie, D. W. (Veterinary and Comparative Orthopaedics and Traumatology, 2001)
A cranio-lateral curvilinear incision in the skin was centered over the greater trochanter. The subsequent approach to the acetabulum involved blunt dissection and avoided the need for significant muscular incision. The major post-operative complications encountered were fracturing of the proximal (2/37) and distal femur (4/37), caudal neuropathy (2/37) and septic femoral stem loosening (1/37). At two years post-operatively, the morbidity rate was 24% and the mortality rate 19%.A regime of analgesia, involving constant infusion of xylazine, was developed and appeared very effective.Thirty-seven mature Merino wethers were utilized for an evaluation of a new acetabular cup design using a modular cemented total hip replacement system. The ovine model for total hip replacement provided a reliable and manageable method for the evaluation of component design and tissue response.
Keywords: Total hip replacement; sheep model